Analisis Financial Performance melalui Penilaian Efisiensi dan Stabilitas Keuangan PT. Wilmar Cahaya Indonesia pada Tahun 2019 - 2024 - Ida Rif’atul Laily; Yuana Amelia; Anna Marina (Universitas Nusantara PGRI Kediri, 2025)
The purpose of this study is to analyze the financial performance of PT. Wilmar Cahaya Indonesia during the period 2019 to 2024 with a focus on assessing efficiency and financial stability. Efficiency and financial stability are measured based on financial ratio analysis including profitability ratio (Return on Asset/ROA) and activity ratio (Total Asset Turnover/TATO) to assess efficiency, while financial stability is assessed through the solvency ratio (Debt to Equity Ratio/DER) and liquidity ratio (Current Ratio). This study uses secondary data in the form of financial reports from companies listed on the Indonesia Stock Exchange (IDX) and is analyzed quantitatively descriptively to obtain a comprehensive picture of the company's financial condition for six years. The results of the study show that asset utilization efficiency (ROA) fluctuated, decreased but then recovered in 2024. An increase in TATO indicates an improvement in efficiency in generating income from company assets. The company's capital structure is relatively stable with a low DER. The liquidity ratio (Current Ratio) shows a good ability to meet short-term obligations, despite a significant spike in 2022. This study concludes that the financial performance of PT. Wilmar Cahaya Indonesia shows a diverse trend during the study period, so special attention is needed to optimally manage assets and debts and sustainability to improve business performance and sustainability.